DESIGNING ENVIRONMENTALLY SUSTAINABLE RESIDENTIAL COMPLEXES BASED ON GREEN ARCHITECTURE (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The article explores the fundamental and applied aspects of designing ecologically sustainable residential complexes through the integration of green architecture principles. This research highlights the convergence between environmental protection, energy efficiency, architectural aesthetics, and technological innovation in modern urban development. The study provides a scientific justification for ecological construction strategies adapted to the climatic and socio-economic conditions of Uzbekistan, focusing on the reduction of energy consumption, renewable resource integration, bioclimatic planning, passive architectural design, water resource efficiency, waste minimization, and the use of environmentally friendly building materials. A comprehensive interdisciplinary methodology was used, combining architectural design theory, environmental engineering, urban ecology, and sustainable development frameworks. The research demonstrates that applying green architecture principles in the planning and design of residential complexes ensures high ecological stability, improves indoor microclimates, reduces the carbon footprint, and enhances the quality of urban life.